2011
DOI: 10.1021/am1011047
|View full text |Cite
|
Sign up to set email alerts
|

Interface Toughness of Carbon Nanotube Reinforced Epoxy Composites

Abstract: Traditional single-fiber pull-out type experiments were conducted on individual multiwalled carbon nanotubes (MWNT) embedded in an epoxy matrix using a novel technique. Remarkably, the results are qualitatively consistent with the predictions of continuum fracture mechanics models. Unstable interface crack propagation occurred at short MWNT embedments, which essentially exhibited a linear load-displacement response prior to peak load. Deep embedments, however, enabled stable crack extension and produced a nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 18 publications
5
72
0
Order By: Relevance
“…In their study, functionalized CNTs showed significantly higher adhesion strengths resulting in CNT failure rather than pull-out from the surrounding matrix that is commonly experienced for unmodified CNTs. Ganesan et al [26] used a single-fiber pull-out technique to investigate the interfacial shear strength and interfacial fracture energy of individual MWCNTs embedded in various lengths in an epoxy matrix. These reports suggest that the presence of CNTs in epoxy matrix can considerably improve its load carrying capacity when the interfacial adhesion of CNTs to the matrix is maintained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, functionalized CNTs showed significantly higher adhesion strengths resulting in CNT failure rather than pull-out from the surrounding matrix that is commonly experienced for unmodified CNTs. Ganesan et al [26] used a single-fiber pull-out technique to investigate the interfacial shear strength and interfacial fracture energy of individual MWCNTs embedded in various lengths in an epoxy matrix. These reports suggest that the presence of CNTs in epoxy matrix can considerably improve its load carrying capacity when the interfacial adhesion of CNTs to the matrix is maintained.…”
Section: Resultsmentioning
confidence: 99%
“…36 N cm −2 ) [24]. Previous investigations [19][20][21][22][23][24][25][26] have established that strength in nanocomposites can be increased at the nanotube interface owing to nanotube pull-out. This phenomenon explains the increase in shear strength.…”
Section: Introductionmentioning
confidence: 94%
“…, and carbon nanotubes [6,[13][14][15] as hierarchical strengthening and toughening substructures has been recently developed; however, their expensive and laborious methods of synthesis and processing are also known. To overcome this limitation, a simple route was recently found by incorporating cellulose nano crystals (CNC, 0.17% in weight) on a glass fiber surface, increasing the ultimate tensile and flexural strength of the composite system by 10 and 40%, respectively [16].…”
mentioning
confidence: 99%
“…When the sliding velocity is around 10 -8 m/s, corresponding to the pull-out rate in experiment [51], the value of the upper bound is 0.62%, which can be easily reached for functionalized CNTs [5]. Therefore, it is reasonable to assume a perfect bonding between the functionalized CNT and the PE matrix in most cases of modeling at a higher scale.…”
Section: The Interfacial Shear Strength and Criterionmentioning
confidence: 93%